2009
DOI: 10.1002/bsl.853
|View full text |Cite
|
Sign up to set email alerts
|

Neuroscience and the law: Philosophical differences and practical constraints

Abstract: Controversies surrounding the value of neuroscience as forensic evidence are explored from the perspective of the philosophy of mind, as well as from a practical analysis of the state of the scientific research literature. At a fundamental philosophical level there are profound differences in how law and neuroscience view the issue of criminal responsibility along the continuum from free will to determinism. At a more practical level, significant limitations in the current state of neuroimaging research constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
0
3
0
2
Order By: Relevance
“…Related to this issue, recent research found that the addition of fMRI evidence suggesting that a defendant was lying increased verdicts of guilt, although this effect disappeared when the validity of this evidence was questioned (McCabe, Castel, & Rhodes, ). Many scholars have recommended caution with regard to neuroscience in the courtroom (Aronson, ; Garland & Glimcher, ; Martell, ; Moriarty, ). Reeves, Mills, Billick, and Brodie () noted that experts must understand the limitations of brain imaging and make appropriately modest claims in the courtroom.…”
Section: Discussionmentioning
confidence: 99%
“…Related to this issue, recent research found that the addition of fMRI evidence suggesting that a defendant was lying increased verdicts of guilt, although this effect disappeared when the validity of this evidence was questioned (McCabe, Castel, & Rhodes, ). Many scholars have recommended caution with regard to neuroscience in the courtroom (Aronson, ; Garland & Glimcher, ; Martell, ; Moriarty, ). Reeves, Mills, Billick, and Brodie () noted that experts must understand the limitations of brain imaging and make appropriately modest claims in the courtroom.…”
Section: Discussionmentioning
confidence: 99%
“…In a special issue on moral decision making, a case was made for a neurobiological etiology of deficient empathy as occurs with antisocial behavior (Shirtcliff et al, 2009). Martell (2009) cautioned against over-extrapolation from neuroscientific research, especially as applied to legal issues such as criminal responsibility. In the present issue Mü ller provides an updated summary of the main cerebral structures and functional circuits for which evidence suggests a possible role in moral decision making and psychopathy.…”
Section: The Neuroidentity Theorymentioning
confidence: 99%
“…Nevertheless it has long been argued that brain imaging evidence is not appropriate as forensic evidence, especially because one has to make an inference based on group studies, which do not necessarily allow conclusions for a single suspect (Mayberg, 1992(Mayberg, , 1996. Although this problem is circumvented by means of pattern classification on single subject data, the ubiquitous problem is, that in order to ascertain mens rea, the defendant's cognition at the time of the crime or action omission itself has to be measured, and cannot easily be inferred after the fact (Martell, 2009).…”
Section: Practical Implicationsmentioning
confidence: 99%